Pengaruh Prinsip Good Corporate Governance terhadap Kinerja Keuangan pada Wisma Davinci - Desmi Triyanti Purba; Windi Susilawati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the effect of Good Corporate Governance (GCG) principles on financial performance at Wisma Davinci. The population of this study consists of the Regional General Manager and supervisor levels at Wisma Davinci, with a total sample of 30 respondents selected using purposive sampling. The independent variable is Good Corporate Governance (X), while the dependent variable is Financial Performance (Y). Data were analyzed using validity and reliability tests, simple linear regression, partial tests (t-tests), and coefficient of determination (R²) with the assistance of SPSS version 25. The validity test results show that all indicators of the Good Corporate Governance variable have a calculated r-value greater than the r-table value of 0.3610, indicating that the instruments are valid. The reliability test shows Cronbach’s Alpha values of 0.960 and 0.937, which are greater than 0.60, confirming that the instruments are reliable. The simple linear regression analysis indicates that Good Corporate Governance has a positive effect on financial performance, with a regression coefficient (b) of 0.474. The partial test results show that Good Corporate Governance significantly affects financial performance (t-count = [isi t-hitung], p < 0.001). Furthermore, the coefficient of determination (R²) value of 0.837 indicates that Good Corporate Governance explains 83.7% of the variation in financial performance, while the remaining 16.3% is influenced by other variables not included in this research model. These findings confirm that the implementation of Good Corporate Governance plays a crucial role in improving financial performance at Wisma Davinci.